Uses and preference of recreational greenspace by women in Kuala Lumpur - Mansor, Mazlina; Zakariya, Khalilah; Harun, Nor Zalina (Zes Rokman Resources, 2018)
Recreational greenspace benefits many aspects of human health. A large number of studies has found that participation in recreational greenspace brings various benefits such as lowering stress level, encourages more physical activity, opportunities for social interaction, and helps relieve stress and mental fatigue. Surprisingly, recent evidence shows that the effects are particularly significant for women. It infers that women need urban recreational greenspace in their daily lives. Although there are notably significant benefits of recreational greenspace for women, we postulate that women in Malaysia have lack access to greenspace and there are factors that hinder them from frequenting the greenspace in Kuala Lumpur city. To study this, we took a sample of the population of women in several zones in Kuala Lumpur (n=1139). We explore whether how they feel about the greenspace, are they frequenting various greenspace within their neighbourhood and their concern regarding the recreational greenspace. The responses were statistically analysed using the SPSS software. The findings suggest that female respondents in the study zones are deprived of the experience of greenspace due to their limited contact with it, even though they prefer to be in the greenspace. Various concerns about the use of greenspace were highlighted namely on facilities and perceptions related to maintenance, safety and security. These factors may be the hindrances for them to be in contact with the spaces. The effects could lead them to be lack of exercise, poor social relationships and stress, which are known to lead to health problems. The findings found to be useful for evaluating future needs on the city’s recreational greenspace that cater activities specifically for female users. Improving recreational greenspace is essential for women that will give many benefits to them.